Stochastic simulations of calcium contents in sugarcane area - Pereira, Gener T. [UNESP]; Teixeira, Daniel D. B. [UNESP]; Souza, Zigomar M. de; Oliveira, Ismenia R. de; Marques Junior, Jose [UNESP] (Univ Federal Campina Grande, 2015)
The aim of this study was to quantify and to map the spatial distribution and uncertainty of soil calcium (Ca) content in a sugarcane area by sequential Gaussian and simulated-annealing simulation methods. The study was conducted in the municipality of Guariba, northeast of the Sao Paulo state. A sampling grid with 206 points separated by a distance of 50 m was established, totaling approximately 42 ha. The calcium contents were evaluated in layer of 0-0.20 m. Techniques of geostatistical estimation, ordinary kriging and stochastic simulations were used. The technique of ordinary kriging does not reproduce satisfactorily the global statistics of the Ca contents. The use of simulation techniques allows reproducing the spatial variability pattern of Ca contents. The techniques of sequential Gaussian simulation and simulated annealing showed significant variations in the contents of Ca in the small scale.
Keywords: geostatistics; spatial interpolation; sequential Gaussian simulation; simulated annealing